Home.Verilog.Digital Design.Digital Basics.Python.RF Basics.
Previous.
Next.
Custom Search

Legal Disclaimer

Chip Designing for ASIC/ FPGA Design engineers and Students
FULLCHIPDESIGN
Digital-logic Design...  Dream for many students… start learning front-end…

Legal Disclaimer

@TYH :- 4G LTE Long Term Evolution Tutorial, CloudComputing
PICS
Verilog Tutorial.
Get Noticed:- Submit your own content to be published on fullchipdesign.com

Send it to fullchip@gmail.com

Digital Basics Tutorial.
Binary Numbers 1s_complement 2s_complement Binary Subtraction Binary Sub. Ex's Sign_magnitude SignM EX Gray Coding BCD coding Digital gates NAND NOR & XNOR Theorems Boolean Functions BFunc Examples Minterm Maxterm Sum of Minterms Prdt of Maxterms 2 var K-map 3 var K-map 4 var K-map 5 var K-map Prime Implicant PI example K-map Ex's KMap minimization 2 var EX

3 variable K-map, Example -2

Minimize following

 

F(x,y,z) =     (0,1,4,5,6,7)

 

Above is a common format of representing the K-map problems.

 

The numbers 0,1,4,5,6,7 are the location of cells in the 3-var k-map table. Discussed below.  

3 variable K– map with 1 and 0 values assigned to cells.

00

01

4

5

11

10

7

6

 

x’y’z’ = 1

 

 

x’y’z = 1

 

 

x’yz = 0

 

 

x’yz’ = 0

 

 

xy’z’ = 1

 

 

xy’z = 1

 

 

xyz = 1

 

 

xyz’ = 1

 

0

1

x

yz

The K-map for 3 variables is plotted above. You will notice the column for 11 and 10 is inter-changed. This is done to allow only one variable to change across adjacent cells. This adjustment in columns allows in minimization of logic mapped into tables.    

Any adjacent 1, 2, 4 or 8 cells can be grouped to find a minimized logic value.

Following plot will show grouping of adjacent cells.

00

01

4

5

11

10

7

6

 

x’y’z’ = 1

 

 

x’y’z = 1

 

 

x’yz = 0

     

 

x’yz’ = 0

 

 

xy’z’ = 1

 

 

xy’z = 1

 

 

xyz = 1

 

 

xyz’ = 1

 

0

1

x

yz

The two step minimization equation is shown below.
With reference to the table above the cells under the dotted box’s can be combined to come up with following reduced  equation.

F = (x’y’z’+ x’y’z + xy’z’ + xy’z) + (xy’z’ + xy’z + xyz + xyz’)
F = (y’ + x)
... Final Answer.
x’y’z’
x’y’z
x’yz
x’yz’
xy’z’
xy’z
xyz
xyz’
1. F(x,y,z) =     (0,1,6,7) - Minimization, on this page.
2. F(x,y,z) =     (0,1,4,5,6,7) - Minimization from here.
3. F(x,y,z) =     (3,4,6,7) - Minimization from here.
4. F(x,y,z) =     (0,1,2,3,4,5,6,7) - Minimization from here.